Value of [18F]fluorodeoxyglucose positron emission tomography in the management of follicular lymphoma: the end of a dilemma? - Janíková, Andrea; Bolčák, Karol; Pavlík, Tomáš; Mayer, Jiří; Král, Zdeněk (Clinical lymphoma & myeloma, 2008)
BACKGROUND: [18F]Fluorodeoxyglucose (FDG) positron emission tomography (PET) is a powerful tool for the imaging of various lymphomas. Despite its high FDG avidity, there is little data on PET in follicular lymphoma (FL). In this work, we present findings concerning PET at staging and posttreatment evaluation in FL. PATIENTS AND METHODS: A total of 181 PET scans were evaluated in 117 patients with FL in a retrospective study. Positron emission tomography-based results were compared with conventional staging in 82 patients. Posttreatment PET evaluation was performed in 99 patients; there were comparable progression-free survivals of PET-positive and PET-negative patients. RESULTS: Positron emission tomography showed more involvement than computed tomography (CT) with clinical examination in 41 of 82 patients (50%), less in 11 of 82 (13%); the same extension was found in 27 of 82 patients (33%), and 3 patients revealed discordant foci visible on PET only and lymphadenopathy without PET activity (P < .001). Including the results of trephine biopsy, PET finally upstaged FL in 15 of 82 patients (18%), which was projected in change of treatment strategy. There were 73 of 99 negative posttreatment PET scans; 54 of 73 PET-negative patients (74%) remain in complete remission (median follow-up, 27 months); 19 (26%) of them relapsed with median of 12 months. Fourteen of 20 (70%) PET-positive patients relapsed with a median of 4.5 months regardless of findings on CT and subsequent therapy. The difference in relapse rates between PET-positive and PET-negative patients is statistically significant (P < .001). CONCLUSION: Positron emission tomography at staging is able to substantially change treatment strategy in an important proportion of patients with FL. Persisting PET positivity after treatment predicts for a high risk of an early relapse and can identify patients with poor prognosis.
Keywords: financování organizované; dospělí; Recurrence; Female; Adult; výsledek terapie; ženské pohlaví; přežití bez známek nemoci; fluorodeoxyglukosa F18; lidé; Lymphoma, Follicular; spontánní regrese nádoru; staging nádorů; recidiva; Treatment Outcome; následné studie; prognóza; Financing, Organized; retrospektivní studie; Follow-Up Studies; Male; Aged; Neoplasm Regression, Spontaneous; Prognosis; Disease-Free Survival; folikulární lymfom; lidé středního věku; pozitronová emisní tomografie; Fluorodeoxyglucose F18; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Neoplasm Staging; Positron-Emission Tomography; Humans